(3aJGhi GdEeGe CHj GdbGSe GdHQRdi GdeGdcis - (3CHh GdbGSe GdHQRdj GdeGdcjs ((3CMeO Hf eMeO Hf ehSi GdReYGfi GdeGdci GdCRgQi s)
(3ChdgG (B:s
(3hcJH Edjg CdJeS gdGd TYHGf hcGf GdSMGH ade jQg CcKQge hhge EKfGf CfgeG QCjGg NdGd GdSMGH hBNQGf cPdc hge djShG HYOhd s
(3BNQgG (B:s
(3LhGH Yf SDGd (B: (3Yef gh ai hdGjI CeI HhUjI CHjg aJRhL EeQCI HZjQ EPfgG adeG YdeJ Hg aSNJg fXQkG Ke ONd Ydi GdeQCI hMedJ efg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1221s
Keywords: (3Gdabg GdeGdcjs